The contents and contours of contemporary cosmopolitan constitution-making: Immanuel Kant in the twenty-first century. Issue 2 (13th June 2019) - QERIMI, QERIM
Abstract: This article articulates legal and practical discourse that seek to apply and extend the classic cosmopolitan ideals of Immanuel Kant to the evolving practice and reality of the twenty-first century. It identifies five major strands through which cosmopolitan law ideals express themselves in contemporary constitution-making, forming in turn the major composite cosmopolitan contents. In some sense, the proposed framework re-imagines Kant in the twenty-first century, mirroring a conjoined classic and contemporaneous concept of cosmopolitan constitution-making. Kantian cosmopolitanism is reinterpreted by way of conjoining the classic cosmopolitan moral and normative principles of universal freedom, human worth and global justice to emerging and actual contemporaneous constitution-making trends such as using international or comparative foreign models as a basis for constitutional design, using international law and foreign domestic law in national constitutional interpretation, or using regional or international bodies of adjudication and their jurisprudence as a constitutionally mandated source of law. The outlined framework seeks to transcend the occasional historical setbacks and sceptical objections to cosmopolitanism, while admitting their continuous, albeit gradually unobtrusive presence. This framework is naturally predisposed to be deferential to a bold imaginative project, such as the one embodied in the Kantian vision of cosmopolitanism, which is both rooted in and survived the historical forces that ran contrary to the cosmopolitan ideals, to reach a point of its ever closer materialisation.